Problematika dan Urgensi Hukum Kecerdasan Buatan Ditinjau dari Hukum di Indonesia - I Gede Adhi Suwarmas Kawiswara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The industrial revolution 4.0 has brought rapid advances in technology, one of which is artificial intelligence (AI). AI has the ability to imitate the human thought and action process in solving various problems. However, the implementation of AI raises legal problems related to responsibility for the negative impacts caused, such as cybercrime, information manipulation, privacy violations, and misuse of technology. Indonesia, as a country based on law, is faced with the challenge of regulating AI to be in line with technological developments. Currently, legal regulations in Indonesia do not specifically regulate the legal responsibility of AI. Positive laws, such as the Civil Code and the ITE Law, can be used interpretively, but are not enough to address the complexity of AI. Legal responsibility related to AI is debatable, whether it is imposed on the developer, owner, or user of AI. In addition, AI does not have a “mens rea” in criminal law, so that unlawful acts are more relevant to be imposed on the responsible human. To overcome this problem, legal reform or the creation of special regulations that comprehensively regulate AI are needed. These regulations must include privacy protection, data security, and criminal and civil liability due to the use of AI. With a clear legal framework, the risk of AI misuse can be minimized and its use can be optimized for the welfare of society.